1982
DOI: 10.1159/000176549
|View full text |Cite
|
Sign up to set email alerts
|

Absorptionsveränderungen von Mangan während Gravidität und Laktation

Abstract: Model studies were conducted using isolated everted sacs of small intestines of rats to test the absotion of manganese during pregnancy and lactation. The intestinal transfer of manganese to the serosal solution and the uptake of manganese into the intestinal wall were measured. The results agree well and yield a comparable pattern of absorption. The Mn absorption rises only slightly in the first and second third of gestation (6th and 12th days of gestation). In the third part of pregnancy (18th day), however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…Previous studies have shown maternal blood Mn levels were increased during pregnancy [ 10 , 35 , 36 ]. The increase in Mn levels during pregnancy may be related to physiological factors, including increased intestinal absorption or tissue Mn mobilization [ 37 , 38 ], reflecting increased need from the fetal development. Takser et al [ 10 ] reported that blood Mn concentration in pregnant women at delivery was higher than non-pregnant women of reproductive age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown maternal blood Mn levels were increased during pregnancy [ 10 , 35 , 36 ]. The increase in Mn levels during pregnancy may be related to physiological factors, including increased intestinal absorption or tissue Mn mobilization [ 37 , 38 ], reflecting increased need from the fetal development. Takser et al [ 10 ] reported that blood Mn concentration in pregnant women at delivery was higher than non-pregnant women of reproductive age.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in blood Mn during pregnancy could be related to an increase in Mn intestinal absorption 4143 or changes in Mn metabolism. 41 It could also result from physiological factors such as differences in tissue Mn mobilization due to increased estrogen and progesterone concentrations during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in the mean whole blood manganese levels throughout the pregnancy period were reported previously [32,40,41] . This increase in manganese levels may be related to the enhanced absorption of manganese due to upregulation of iron absorption, particularly during the late pregnancy periods [42,43] , because mechanisms of iron absorption are similar to those of other divalent metals, particularly manganese and cadmium [4,5] . However, age-related increase in blood manganese is not observed [11] , because its absorption, disposition, and biliary excretion are actively controlled by homeostatic mechanisms as an essential element [30] .…”
Section: Manganesementioning
confidence: 99%